Earnings quality and firm value: Does corporate governance matter? - Panern Intara; Klangjai Sangwichitr; On-anong Sattayarak (Cogent Business & Management, 2024)
This study examines the relationship between earnings quality and the firm value of listed companies in the Stock Exchange of Thailand (SET) in the property and construction sector. This research further investigates whether effective corporate governance (CG) mechanisms enhance the relationship between earning quality (measured by the accruals component and total accruals) and firm value (measured by Tobin's Q). The information is gathered from 84 listed companies comprising 672 firm-year observations covering the period from 2014 to 2021. The empirical findings indicate a statistically significant positive relationship between earnings quality and firm value. We discover that firms with strong CG tend to experience a stronger positive relationship between earnings quality and firm value than those with weak CG. The results are robust different proxies for firm value measurement.
Keywords: 650; Earnings quality; firm value; corporate governance